BUDAYA DAN PENDIDIKAN KARAKTER PADA PESANTREN CAMPURAN DI PONDOK PESANTREN MIFTAHUL HIDAYAH KABUPATEN GARUT - Ahmad Jaelani (Jurnal Tarbiyatuna : Kajian Pendidikan Islam, 2021)
The purpose of this article is to find out the culture and character education at Miftahul Hidayah boarding school in Garut Regency. This boarding school combines salaf and modern pesantren patterns. Pesantren also makes pesantren culture as a medium of character building santri. The focus of the issues studied was about pesantren culture, character education and management of Miftahul Hidayah boarding school. The results showed that the culture of Miftahul Hidayah boarding school in building santri character through pesantren culture was very good and successfully observed from the character of santri in the field of science, morals and social. So that with character education built pesantren through pesantren culture makes santri not jumud in all fields, especially in the millennial era now.